Current Directions and Developments in Research on Environmentally Friendly Food Consumer Behavior: A Systematic Literature Review : Arah dan Perkembangan Terkini Penelitian Perilaku Konsumen Pangan Ramah Lingkungan: Systematic Literature Review - Juli Winando Lumban Toruan (Jurnal Ilmiah Sosio Agribis, 2026)
The environmental impact of global food production has increased academic attention to environmentally friendly food consumer behavior. This study analyzes the direction and recent developments in this research field using a Systematic Literature Review (SLR) approach. Data were obtained from the Scopus database, covering 81 articles published between 2015 and 2026. Bibliometric analysis was conducted using VOSviewer to visualize keyword co-occurrence and thematic evolution. Results show a significant increase in publications, peaking in 2025. Key themes identified include consumer behavior, consumer attitude, sustainable food consumption, and sustainable development. Thematic evolution reveals a shift from early studies focused on environmental awareness and consumer attitudes toward more complex issues, such as determinants of environmentally friendly purchasing behavior, sustainable food innovation, eco-labels, digital communication, and sustainable supply chain systems. These emerging themes indicate that research is moving beyond individual awareness to include technological, informational, and systemic factors influencing consumption decisions. Overall, this study concludes that research on environmentally friendly food consumer behavior is developing toward a more integrated and multidisciplinary approach, combining insights from marketing, environmental psychology, food science, and supply chain management.